PEMBERDAYAAN PETANI KELAPA SAWIT DI DESA TIANG TARA MELALUI PELATIHAN GOOD AGRICULTURAL PRACTICES - Bahtera, Novyandra Ilham; Yulia, Yulia; Herza, Herza (Universitas Mataram, 2024)
Tiang Tara Village in Bakam District, Bangka Regency, has an area of 4,954 hectares with 61.6% used for oil palm plantations. The village faces various challenges in the agricultural sector, especially for oil palm smallholders who have difficulty competing in international markets, lack understanding of Good Agricultural Practices (GAP), and face long supply chains. In addition, smallholders are also hampered by low socio-economic conditions, limited access to technology, and a lack of agricultural knowledge. This empowerment program aims to improve farmers' knowledge and skills through socialization, training, and mentoring in the application of GAP. The targets of this program include increased GAP knowledge and adoption of GAP practices by farmers. The program implementation methods included collaboration with various parties, socialization, intensive training, and technical assistance. Evaluation was conducted through questionnaires to measure the success of the program and obtain feedback from participants. The results showed that the majority of farmers were over 40 years old with low formal education, which affected their understanding of GAP. Currently, the average production of oil palm was still low and farmers' income was insufficient. Through this program, farmers' knowledge and skills in oil palm cultivation are improved, which is expected to increase the productivity and welfare of farmers in Tiang Tara Village.